POTENTIAL THERAPEUTIC ROLE OF ROBINETIN AGAINST PARAQUAT-INSTIGATED HEPATIC TOXICITY VIA REGULATING NRF-2/KEAP-1, OXIDATIVE STRESS AND INFLAMMATION - Naila Ghafoor; Muhammad Zaid Salar; Asma Ashraf; Muhammad Faisal Hayat; Moazama Batool; Hamida Hamdi (Journal of Animal and Plant Sciences, 2026)
Paraquat (PQ) is an extensively used herbicide throughout the world, which is extremely harmful to living organisms. Robinetin (ROB) is a naturally occurring flavonoid with reported pharmacological potential. The current research was focused on identifying the hepato-protective potential of ROB against PQ-intoxicated liver damage in rats. The animals were randomly divided into four groups following a completely randomized design (CRD); control, PQ (5 mgkg-1) group, PQ (5 mgkg-1) + ROB (30 mgkg-1) group and only ROB (30 mgkg-1) supplemented group.  The results of the current trial demonstrated that PQ exposure reduced the expressions of NRF-2 and antioxidant enzymes while elevating the expressions of KEAP-1. Additionally, PQ exposure decreased the enzymatic activities of glutathione reductase (GSR), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferase (GST) as well as glutathione (GSH) content while increasing malondialdehyde (MDA) and reactive oxygen species (ROS) levels, which indicated oxidative stress (OS) in the PQ administered group. Furthermore, PQ exposure increased the levels of liver serum enzyme i.e., AST, ALP and ALT. Moreover, PQ administration increased the levels of inflammatory cytokines, including NF-κB, TNF-α, COX-2, IL-1β, and IL-6. Besides, CASPASE-3 and BAX (pro-apoptotic markers) expressions were augmented while BCL-2 (anti-apoptotic marker) expressions were reduced due to PQ exposure. Furthermore, PQ treatment led to multiple histopathological damages in the hepatic tissues. However, ROB supplementation markedly restored the abovementioned alterations due to its anti-apoptotic, antioxidative and anti-inflammatory potentials.
Keywords: Paraquat; Robinetin; Oxidative stress; Hepatic damages; Antioxidant; Reactive Oxygen Species